Identification and characterization of the glucose dual-affinity transport system in Neurospora crassa: pleiotropic roles in nutrient transport, signaling, and carbon catabolite repression. Issue 1 (December 2017) - Wang, Bang; Li, Jingen; Gao, Jingfang; Cai, Pengli; Han, Xiaoyun; Tian, Chaoguang
Abstract Background The glucose dual-affinity transport system (low- and high-affinity) is a conserved strategy used by microorganisms to cope with natural fluctuations in nutrient availability in the environment. The glucose-sensing and uptake processes are believed to be tightly associated with cellulase expression regulation in cellulolytic fungi. However, both the identities and functions of the major molecular components of this evolutionarily conserved system in filamentous fungi remain elusive. Here, we systematically identified and characterized the components of the glucose dual-affinity transport system in the model fungusNeurospora crassa . Results Using RNA sequencing coupled with functional transport analyses, we assigned GLT-1 (K m = 18.42 ± 3.38 mM) and HGT-1/-2 (K m = 16.13 ± 0.95 and 98.97 ± 22.02 µM) to the low- and high-affinity glucose transport systems, respectively. The high-affinity transportershgt -1/ -2 complemented a moderate growth defect under high glucose whenglt -1 was deleted. Simultaneous deletion ofhgt -1/ -2 led to extensive derepression of genes for plant cell wall deconstruction in cells grown on cellulose. The suppression by HGT-1/-2 was connected to both carbon catabolite repression (CCR) and the cyclic adenosine monophosphate-protein kinase A pathway. Alteration of a residue conserved across taxa in hexose transporters resulted in a loss of glucose-transporting function, whereas CCR signal transduction was retained, indicating dual functions for HGT-1/-2 as "transceptors." Conclusions In this study, GLT-1 and HGT-1/-2 were identified as the key components of the glucose dual-affinity transport system, which plays diverse roles in glucose transport and carbon metabolism. Given the wide conservation of the glucose dual-affinity transport system across fungal species, the identification of its components and their pleiotropic roles in this study shed important new light on the molecular basis of nutrient transport, signaling, and plant cell wall degradation in fungi.